TREATMENT OF FINANCIAL STATEMENTS USING THE CAMEL RATIO METHOD TO ASSESS FINANCIAL PERFORMANCE AT BRI BANK REGISTERED AT OJK - Enny Istanti (Jurnal Akuntansi dan Pajak, 2023)
A bank is a bank that has an important role in the economy in a country, therefore a healthy bank is needed. To assess the soundness of a bank using the CAMEL method, this is in accordance with the regulations issued by Bank Indonesia. The purpose of this study was to determine the level of soundness of Bank Rakyat Indonesia (BRI) in the period 2017-2019, which is a State-Owned Enterprise (BUMN). The research method used is the CAMEL ratio method (CAR, KAP, NPM, ROA & BOPO, LDR). The results of the research in the last 3 years after being measured with the applicable standard Bank Indonesia regulations, it was found that the average soundness level of BRI Banks is Fairly Healthy Keywords: Capital, Assets, Management, Income, Liquidity